Distribusi Pendapatan dan Kemiskinan di Indonesia: Kasus Kebijakan Sentralisasi, Desentralisasi, dan Pandemi Covid-19 - Salim Fauzanul Ihsani; M. Fathur Rohman (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This article reviews the problem of income distribution and poverty in Indonesia based on the case of policies in the era of centralization, decentralization, and the COVID-19 pandemic. This article was compiled using the literature study method. The Centralization period began with good results until the late 1980s and early 1990s there were problems with income distribution and poverty, and then exacerbated by the 1997-1998 economic crisis. The decentralization period began with an upward trend in income inequality after 1998, but empirically, fiscal decentralization has proven to be better at reducing regional income inequality. The existence of the Covid-19 Pandemic has a very large impact on economic growth, reduced community economic activity makes economic growth decline, The decline in economic growth causes an increase in the poverty rate. The Covid-19 pandemic caused high inequality in urban areas, but not too high at the rural level, this indicates that inequality in urban areas is much more serious than rural areas. The policy strategy needed to address the problem of income distribution and poverty should pay attention to aspects of institutional intervention policies, sustainable fiscal policies, special policies for the very poor, and equitable development policies. The Presidential Instruction on Disadvantaged Villages (IDT), Economic Equity Policy (KPE), and National Economic Recovery (PEN) are 3 important policies that have been carried out by the government in overcoming the problem of income distribution and poverty in Indonesia.